PENINGKATAN KOMPETENSI GURU MENERAPKAN PEMBELAJARAN BERDIFERENSIASI UNTUK MEWUJUDKAN MERDEKA BELAJAR MELALUI LOKAKARYA DI SMPN 3 PONTIANAK - Subhan Subhan (Jurnal Pembelajaran Prospektif, 2022)
Minister of Education and Culture, Nadiem A. Makarim has decided about the education policy program, known as “Merdeka Belajar’. The most essential thing by its policy in SMP 3’s learning management is about New Student Member Admission with Zoning System. It leads to affect student members intake to be more diversification. However, student membersintake above 80, and they were having equal academically capable of in the previous. Moreover, the teacher already felt a few indications as a gap impact by that policy such as complaining about student mischief, goal decrease, and laziness. If its discourse were ignored, it could decrease school achievement. The formulation of the problem in this research was how teachers compile learning management capability escalation, implement differentiated instruction, and how student wellbeing as ‘MERDEKA Belajar’ representation on SMP 3 workshop in the academic year 2021/2022. Its problem solving was conducted in Action Research. The Research indicates that (1) Teacher competence in conducting differentiated lesson plan increase from cycle I to cycle II. The average value ofcycle I achieve 91,77 excellent categories (A) and increase on cycle II to be 97,02 with excellent category (A). Teacher capability implementing differentiated instruction rise from cycle I to cycle II. The average value of cycle I achieves 73,28 with good category (B) increase on cycle II to be 96,00 with excellent category (A). Merdeka Belajar Student wellbeing as an impact of differentiated-instruction implementation increases from cycles Ito II. Cycle I gain 78 good categories (B) increase on cycle II to be 83 good categories (B).